Evaluate the stroke awareness of Palestinian undergraduate health students: A cross-sectional study on risk factors and warning signs - Mohammad Abuawad; Motaz Saifi; Maha Rabayaa; Mustafa Ghanim; Malik Alqub; Tartil Zarura; Diana Aldeek; Jomana Khateeb; Salah Abu Khalaf; Majdi Dwikat; Samar Alkhaldi; Johnny Amer; et al. (PLoS ONE, 2025)
Background Adequate knowledge of the clinical conditions associated with stroke, including risk factors and warning signs, is critical for improving healthcare outcomes. This study assesses undergraduate health students’ knowledge and attitudes toward stroke, including risk factors and warning signs. Methods A descriptive cross-sectional study was conducted with 1006 Palestinian undergraduate health students from several universities enrolled in medicine, pharmacy, nursing, and other health-related disciplines between March 2024 and July 2024. A validated self-administered questionnaire from previous publications was used to assess knowledge of stroke risk factors and warning signs. Attitudes were assessed using a Likert scale. The data were analyzed via SPSS 21 for Windows. Frequencies and percentages were used to summarize demographic data, whereas chi-square tests were performed to assess the associations between demographic characteristics and participants’ knowledge scores (good/poor). Results Among the 1006 participants, 55.4% were females, and 37.5% were in their third academic year. More than 65% of the participants were aware of the stroke-affected organ and the most affected gender. Awareness of key stroke risk factors including hypertension, smoking, alcohol consumption, diabetes mellitus, family history, previous strokes, obesity, and high cholesterol was high. The students’ knowledge scores varied significantly by gender, academic year of study, place of residence, and field of education (p-value <0.05). Having good knowledge about stroke was significantly greater in females than in males (OR: 2.699), and was greater in sixth- and fourth-year students than in second-year students (OR: 6.855 and 1.704, respectively). However, it was significantly lower among health science students compared to preclinical medicine students (OR: 0.257). Conclusion The current findings highlight the need for focused educational interventions, as medical students have greater awareness of stroke than their peers. Enhancing stroke awareness among health students is essential for facilitating early diagnosis and proper healthcare aid. Thus, targeting gaps in knowledge among health students should be part of broader efforts to improve stroke awareness.